2021
DOI: 10.1186/s40959-021-00100-3
|View full text |Cite
|
Sign up to set email alerts
|

Damage to cardiac vasculature may be associated with breast cancer treatment-induced cardiotoxicity

Abstract: Background Breast cancer is the most common female cancer worldwide. Effective therapies including doxorubicin and trastuzumab have improved survival, but are associated with a substantial risk of cardiovascular disease. Mechanisms underlying cancer treatment-induced cardiotoxicity (CTC) are poorly understood and have largely focused on cardiomyocyte damage, although other cellular populations in the heart such as the cardiac endothelium, may play an important role in cardiac damage. We treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…Whereas the doses of the drug in the clinical setting are determined using patients’ body surface area, ratio of body surface area to body mass and the rates of doxorubicin metabolism are vastly different in mice, as compared with humans. The dose of 5 mg/kg used in the present study was reported by others ( 71 ) to steadily reduce breast tumor volumes in mice and therefore regarded as clinically relevant. We found that at this dose, cardiac endothelial cells had higher nuclear concentrations of doxorubicin compared with other cells, and thus likely constitute a target of doxorubicin in the heart.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Whereas the doses of the drug in the clinical setting are determined using patients’ body surface area, ratio of body surface area to body mass and the rates of doxorubicin metabolism are vastly different in mice, as compared with humans. The dose of 5 mg/kg used in the present study was reported by others ( 71 ) to steadily reduce breast tumor volumes in mice and therefore regarded as clinically relevant. We found that at this dose, cardiac endothelial cells had higher nuclear concentrations of doxorubicin compared with other cells, and thus likely constitute a target of doxorubicin in the heart.…”
Section: Discussionmentioning
confidence: 81%
“…Endothelial cells account for over 60% of non-myocyte cells and are the most abundant cell type in the heart ( 72 ). Several recent studies have also emphasized an important role of endothelial cells in development of doxorubicin cardiomyopathy ( 19 , 71 , 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…To explore the potential of MM1-EVs in combination with DOX in vivo, we generated an orthotopic mouse model of breast cancer by implanting 4T1 cells in the fourth left breast of BALB/c mice. M1-DOX and MM1-DOX were used at a concentration of 2 mg/kg and compared with free DOX at a dose of 5 mg/kg, which had been previously established as an effective dose to reduce tumor growth in this breast cancer model [ 30 ]. The experiment revealed that all samples were able to reduce tumor growth when compared to the groups treated with saline solution.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to their well-known cardiovascular side effects and comparatively high incidence of heart failure, anthracyclines have been the most extensively researched medication for decades [ 67 ]. Hoffmann et al [ 68 ] reported that doxorubicin and trastuzumab treatment of nude mice in an orthotopic mouse model of human breast cancer led to a cardiovascular defect. In order to effectively treat cancer, new strategies are urgently needed to prevent potential cardiovascular diseases.…”
Section: Cancer Treatment-induced Cardiovascular Toxicitymentioning
confidence: 99%